Migration in an enlarged EU: a challenging solution? - Martin Kahanec; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The 2004 and 2007 enlargements of the European Union were unprecedented in a number of economic and policy aspects. This essay provides a broad and in-depth account of the effects of the post-enlargement migration flows on the receiving as well as sending countries in three broader areas: labour markets, welfare systems, and growth and competitiveness. Our analysis of the available literature and empirical evidence shows that (i) EU enlargement had a significant impact on migration flows from new to old member states, (ii) restrictions applied in some of the countries did not stop migrants from coming but changed the composition of the immigrants, (iii) any negative effects in the labour market on wages or employment are hard to detect, (iv) post-enlargement migration contributes to growth prospects of the EU, (v) these immigrants are strongly attached to the labour market, and (vi) they are quite unlikely to be among welfare recipients. These findings point out the difficulties that restrictions on the free movement of workers bring about.
Keywords: F22; J15; J61; 330; Migration; migration effects; EU Eastern enlargement; free movement of workers; EU-Erweiterung; Internationale Wanderung; Internationale Arbeitsmobilität; Freizügigkeit; EU-Staaten; EU-Staaten (Osteuropa)